Carbamylation of Integrin αIIbβ3: The Mechanistic Link to Platelet Dysfunction in ESKD. Issue 10 (October 2022) - Binder, Veronika; Chruścicka-Smaga, Barbara; Bergum, Brith; Jaisson, Stéphane; Gillery, Philippe; Sivertsen, Joar; Hervig, Tor; Kaminska, Marta; Tilvawala, Ronak; Nemmara, Venkatesh V.; Thompson, Paul R.; Potempa, Jan; et al.
Significance Statement: Dialysis is lifesaving for patients with ESKD, but replaces only 10% of normal kidney function, leaving these patients with a chronic urea overload. One unavoidable consequence of excess urea is carbamylation, a post-translational modification that interferes with biologic functions of proteins. In this study, the authors found that platelets from patients with ESKD exhibit carbamylation-triggered structural alterations in integrin α IIb β 3, associated with a fibrinogen-binding defect and impaired platelet aggregation. Given that lysine 185 in the β 3 subunit seems to play a pivotal role in receptor activation, carbamylation of this residue may represent a mechanistic link between uremia and dysfunctional primary hemostasis in patients. Supplementation of free amino acids prevented loss of α IIb β 3 function, suggesting amino acid administration may have a beneficial effect on uremic platelet dysfunction. Visual Abstract: Abstract : Background: Bleeding diatheses, common among patients with ESKD, can lead to serious complications, particularly during invasive procedures. Chronic urea overload significantly increases cyanate concentrations in patients with ESKD, leading to carbamylation, an irreversible modification of proteins and peptides. Methods: To investigate carbamylation as a potential mechanistic link between uremia and platelet dysfunction in ESKD, we used liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) to quantify total homocitrulline, and biotin-conjugated phenylglyoxal labeling and Western blot to detect carbamylated integrin α IIb β 3 (a receptor required for platelet aggregation). Flow cytometry was used to study activation of isolated platelets and platelet-rich plasma. In a transient transfection system, we tested activity and fibrinogen binding of different mutated forms of the receptor. We assessed platelet adhesion and aggregation in microplate assays. Results: Carbamylation inhibited platelet activation, adhesion, and aggregation. Patients on hemodialysis exhibited significantly reduced activation of α IIb β 3 compared with healthy controls. We found significant carbamylation of both subunits of α IIb β 3 on platelets from patients receiving hemodialysis versus only minor modification in controls. In the transient transfection system, modification of lysine 185 in the β 3 subunit was associated with loss of receptor activity and fibrinogen binding. Supplementation of free amino acids, which was shown to protect plasma proteins from carbamylation-induced damage in patients on hemodialysis, prevented loss of α IIb β 3 activity in vitro . Conclusions: Carbamylation of α IIb β 3 —specifically modification of the K185 residue—might represent a mechanistic link between uremia and dysfunctional primary hemostasis in patients on hemodialysis. The observation that free amino acids prevented the carbamylation-induced loss of α IIb β 3 activity suggests amino acid administration during dialysis may help to normalize platelet function.